Imagine! 100 years of international surrealism - Gaßner, Hubertus 1950-; Görgen-Lammers, Annabelle 1969-; Ottinger, Didier 1957-; Sarré, Marie; Scopelliti, Paolo; Vagnoni, Francesca; Vandepitte, Francisca (Royal Museums of Fine Arts of Belgium, 2024)
100 years after the publication of André Breton’s Manifeste du Surréalisme, The Royal Museums of Fine Arts of Belgium celebrate a century of international surrealism with the extraordinary exhibition IMAGINE! From Giorgio de Chirico to Jackson Pollock, Salvador Dalí, René Magritte, Joan Miró, Dorothea Tanning, Man Ray and Leonor Fini: the exhibition and accompanying book offer an immersion in surrealist poetry, dream, the labyrinth, metamorphosis, the unknown and the subconscious, led by the great names of the surrealists. IMAGINE! explores surrealism from a symbolist perspective, through more than 130 works of art (paintings, works on paper, sculptures, objects, assemblages, and photographs), focusing on the connections and similarities, and the differences between surrealism and symbolism, one of its precursors. From 1880 onwards, Brussels was an exceptional hub for the arts and the avant-garde, as demonstrated by the exhibitions of groups such as "Les XX" and "La Libre Esthétique". Symbolism, embodied in particular by Rops, Spilliaert, Khnopff, Delville and Minne, evolved rapidly in Brussels and largely anticipated the emergence of the surrealist movement. A few decades later, Brussels became a centre for Belgian surrealism. Despite the cultural rupture caused by World War I, the older symbolists and the emerging youth were never fundamentally alienated from each other. After Brussels, the exhibition will travel to the Centre Pompidou in Paris, the Hamburger Kunsthalle and the Fundación Mapfré Madrid, before closing at the Philadelphia Museum of Art
Impressum: This book accompanies the exhibition "IMAGINE! 100 Years of International Surrealism" organised by the Royal Museums of Fine Arts of Belgium from 21 February until 21 July 2024. It is published in English, French and Dutch. The exhibition is organised to celebrate the centenary of the publication of the Manifesto of Surrealism, in partnership with the Centre Pompidou, Paris (4 September 2024 - 13 January 2025), the Fundación MAPFRE, Madrid (4 February - 11 May 2025), the Hamburger Kunsthalle, Hamburg (12 June - 12 October 2025) and the Philadelphia Museum of Art (autumn 2025 - spring 2026)
Keywords: Surrealismus; Ausstellungskatalog -- Musées royaux des Beaux-Arts de Belgique -- 21.02.2024-21.07.2024 -- Brüssel; Ausstellungskatalog -- Centre Pompidou -- 04.09.2024-13.01.2025 -- Paris; Ausstellungskatalog -- Fundación MAPFRE -- 04.02.2025-11.05.2025 -- Madrid; Ausstellungskatalog -- Hamburger Kunsthalle -- 12.06.2025-12.10.2025 -- Hamburg; Ausstellungskatalog -- Philadelphia Museum of Art -- 2025-2026 -- Philadelphia, Pa.